Relationship between microbiota in the goldfish gut and fish digestive physiology: A meta-analysis approach - Choirunisa, Evifa Lutfiah Sya'bani; Zulfah, Kayla Fatimah; Fathiyya, Adinda Zhafarah; Rusdi, Rusdi; Lisanti, Elsa (Acta Aquatica: Aquatic Sciences Journal, 2025)
The fish intestinal microbiota is associated with the fish's health status. This study aims to determine the relationship of the fish intestinal microbiota with the fish's physiological digestion. Methods used in this study are meta-analysis by collecting sources of relevant articles or journals with the research topic. The data is secondary data obtained from the process of analyzing articles or journals that have been obtained. The results showed that the type of microbiota is not different in each species of fish but the number of microbiota is different in each species of fish. The absence of differences is because this study only takes data from the dominant types of microbiota in each fish species, while differences in the number of microbiota are due to differences in environmental conditions, eating habits, fish health, fish species, and fish age. Some types of microbiota that become dominant and will be commonly found in various types of fish are Actinobacteria, Bacteroidetes, Firmicutes, Fusobacteria, and Proteobacteria. The presence of each type of microbiota will have different impacts and functions for the host. Keywords: Turtle, Rainfall, Wind Speed, Wave Height.Keyword: Digestive Physiology; Goldfish; Intestine Microbiota